Request strategies in email communication in a private institution / Marchie Lim Pin Sim - Lim, Marchie Pin Sim (2012)
This paper investigates the ways in which staff members in the workplace of a private institution in Malaysia, realise requests in their email communications with special reference to politeness strategies as described by Brown and Levinson (1987) complemented by Spencer-Oatey’s (2008) rapport management framework. It provides a pragmatic analysis of the strategies of requests speech act and politeness phenomenon in the production of request speech acts in the emails by staff members. It aims to identify the politeness strategies employed with regards to face and rapport management by staff members of different professional status when making requests in their email communication with staff members of different positions of power. It explores the lexical choices used to indicate politeness in the request emails and investigates the politeness markers used in greetings, closings and the requests phrases. It seeks to find out if there is a difference in the way they construct their sentences or whether the same structures are used when communicating with people of different positions in an attempt to analyse the correlation between social distance and the politeness strategies employed and the institutional social norms for rapport management. It also seeks to establish if recipients accommodate to politeness elements in their replies. The paper is based on the analysis of fifty request emails written by four staff members to their subordinates, peers and superior and the responses to the requests. The study is descriptive in nature and frequencies and qualitative analysis are used. The findings of the study revealed that staff members use similar forms of structural and verbal politeness forms in opening, closing and requests phrases of their emails. In their requests, they tend to use negative politeness strategies, especially with superiors or peers and direct strategies with subordinates in their requests, mitigated with politeness markers. There is a tendency to use hedges in the negative politeness strategies. It was also found that recipients accommodate politeness in their reply emails. These negative politeness strategies and mitigators are also found to function as linguistic devices to build rapport among the institution’s staff members.